Serum selenium status in Graves' disease with and without orbitopathy: a case–control study. (30th January 2014) - Khong, Jwu Jin; Goldstein, Rebecca F.; Sanders, Kerrie M.; Schneider, Hans; Pope, Jeffrey; Burdon, Kathryn P.; Craig, Jamie E.; Ebeling, Peter R.
Summary Objective Selenium is effective in improving quality of life and reducing the progression of active Graves' orbitopathy. The effect of correcting relative selenium deficiency on improving Graves' orbitopathy is unknown, as baseline selenium levels have not previously been measured. The study aims to determine whether serum selenium levels are reduced in patients with Graves' disease with orbitopathy (GO) compared with without orbitopathy (GD). Design A prospective, case–control study performed between 2009 and 2012 at endocrine and ophthalmology clinics in Australia. Patients A total of 198 patients with Graves' disease participated in the study: 101 with Graves' orbitopathy and 97 without Graves' orbitopathy. Measurements Serum selenium levels in both groups. Results Mean serum selenium levels were significantly lower in GO (1·10 ± 0·18 μm) than in GD (1·19 ± 0·20 μm) (P = 0·001). Mean selenium levels appeared to decrease in parallel with increasing severity of GO; selenium level was 1·19 ± 0·20 μm in GD, 1·10 ± 0·19 μm in moderate‐to‐severe GO and 1·09 ± 0·17 μm in sight‐threatening GO (P = 0·003). Serum selenium levels remained significantly lower in GO after adjusting for age, smoking status, thyroidectomy, radioactive iodine treatment and residential location. Conclusion Serum selenium levels are lower in patients with GO compared with GD in an Australian study population with marginal selenium status. Relative selenium deficiency may be an independent risk factor for orbitopathy in patients with Graves' disease.